At the arrival of the 'Zyrjanin' at Barcelona. Consejero de Abastos por la CNT en la generalidad en 1936/1937. Despues secretario general del Comité Regional CNT de Cataluña. Original in CNT-collection onL 422
At the arrival of the 'Zyrjanin' at Barcelona. Consejero de Abastos por la CNT en la generalidad en 1936/1937. Despues secretario general del Comité Regional CNT de Cataluña. Original in CNT-collection onL 422.